Emergency response to chemical and biological agents - Cashman, John R (Lewis Publishers, 2000)
Terrorists on U. S. Soil.--Chemical agents.--Biological agents and toxins.--Standar operations of hazardous material response teams (HMRTs).--Federal Agencies and responses teams.--Local Haz Mat response teams.--State and regional Haz Mat response teams.--Industry and commercial responses reams.--Urban search and rescue teams and a mass casualty incident in Washington.--Recent U.S incidents involving chemical agents, biological materials.--Research sources and resoueces.